2022
DOI: 10.1155/2022/6452636
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cancer-Associated Fibroblast Subtype of Triple-Negative Breast Cancer

Abstract: Background. There is limited knowledge about the role of cancer-associated fibroblasts (CAF) in the tumor microenvironment of triple-negative breast cancer (TNBC). Methods. Three hundred and thirty-five TNBC samples from four datasets were retrieved and analyzed. In order to determine the CAF subtype by combining gene expression profiles, an unsupervised clustering analysis was adopted. The prognosis, enriched pathways, immune cells, immune scores, and tumor purity were compared between CAF subtypes. The genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…In the remodeling steps during tumor growth, the normal ECM collagens are substituted with a tumor-specific collagen profile [ 70 ]. Increased expression of different collagens was associated with tumor progression and a poor prognosis in various types of epithelial cancers including colorectal [ 71 ], esophagus [ 72 ], glioma [ 73 ], gastric [ 74 , 75 ], head and neck [ 76 ], lung [ 77 ], ovarian [ 78 ], pancreatic [ 79 ], renal [ 80 ], breast [ 81 , 82 ], and cervical cancer [ 83 ]. The profile of different collagen types expressed in various solid cancers is presented as a heatmap in Figure 2 .…”
Section: Collagen Family and Cancermentioning
confidence: 99%
“…In the remodeling steps during tumor growth, the normal ECM collagens are substituted with a tumor-specific collagen profile [ 70 ]. Increased expression of different collagens was associated with tumor progression and a poor prognosis in various types of epithelial cancers including colorectal [ 71 ], esophagus [ 72 ], glioma [ 73 ], gastric [ 74 , 75 ], head and neck [ 76 ], lung [ 77 ], ovarian [ 78 ], pancreatic [ 79 ], renal [ 80 ], breast [ 81 , 82 ], and cervical cancer [ 83 ]. The profile of different collagen types expressed in various solid cancers is presented as a heatmap in Figure 2 .…”
Section: Collagen Family and Cancermentioning
confidence: 99%
“…COL11A1 is a known marker of CAFs [40][41][42][43], but COL10A1 is a novel PDAC CAF marker. COL10A1 has been associated with CAFs in breast cancer [44]. Actually, one study found that a specific CAF subtype in breast cancer, associated with an immunosuppressive TME, was unique in its increased expression of specific collagens, including type VIII, X, and XI collagens [45].…”
Section: Discussionmentioning
confidence: 99%
“…Our 3D TNBC monoculture model may not fully reflect physiological conditions, thus we aimed to investigate the anti-tumor potential of ( 1 ) by mimicking the TNBC TME by inclusion of tumor-specific stromal cells and ECM-matrix components [ 107 ]. Spheroids were grown with additional type I collagen, the main component in the stroma of TNBC patients [ 108 ], mainly secreted by CAFs [ 43 ] and elevated in breast cancer [ 109 ].…”
Section: Discussionmentioning
confidence: 99%